2015
DOI: 10.1186/s12858-015-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme assays for synthesis and degradation of 2-5As and other 2′-5′ oligonucleotides

Abstract: BackgroundThe 5′-triphosphorylated, 2′-5′-linked oligoadenylate polyribonucleotides (2-5As) are central to the interferon-induced antiviral 2-5A system. The 2-5As bind and activate the RNase L, an endoRNase degrading viral and cellular RNA leading to inhibition of viral replication. The 2-5A system is tightly controlled by synthesis and degradation of 2-5As. Whereas synthesis is mediated by the 2′-5′ oligoadenylate synthetase family of enzymes, degradation seems to be orchestrated by multiple enzyme nucleases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The Pig OAS1 produced few dimers compared to the hOAS1 isomers under the 18 h reaction incubation conditions used. The p42, p44, p46, p48 and p52 hOAS1 proteins were previously shown to have 2-5A synthetase activity [14,21,22]. Consistent with our data, a recent study that directly compared the relative activities of partially purified p42, p44, p46, p48 and p52 expressed in E. coli as maltose-binding protein (MBP) fusion proteins, found that all of the isoforms were able to robustly synthesize 2-5A [23].…”
Section: Recombinant Hoas1 P41 P42 P44 P46 P48 P49 and P52 Isofosupporting
confidence: 90%
“…The Pig OAS1 produced few dimers compared to the hOAS1 isomers under the 18 h reaction incubation conditions used. The p42, p44, p46, p48 and p52 hOAS1 proteins were previously shown to have 2-5A synthetase activity [14,21,22]. Consistent with our data, a recent study that directly compared the relative activities of partially purified p42, p44, p46, p48 and p52 expressed in E. coli as maltose-binding protein (MBP) fusion proteins, found that all of the isoforms were able to robustly synthesize 2-5A [23].…”
Section: Recombinant Hoas1 P41 P42 P44 P46 P48 P49 and P52 Isofosupporting
confidence: 90%
“…2-5A was synthesized enzymatically in vitro by recombinant human OAS1. First, recombinant OAS1 (p42) containing an N-terminal His tag was expressed in BL21(DE3) E.coli as described before (Poulsen et al, 2015) or with an alternative protocol using autoinduction media (Studier, 2005). Then cells were collected by centrifugation at 7000 g for 15 min at 4˚C.…”
Section: Methods Detailsmentioning
confidence: 99%
“…To stop the reaction, samples were incubated at 85 ˚C for 15 minutes. Then the samples were filtered (22 µm pore size Millipore filter) and the different 2-5A species were separated on a 16/10 MonoQ column as described before (Poulsen et al, 2015). The same 2-5A fractions from several run was pooled and run again on 16/10 MonoQ column to achieve higher concentrations.…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assays used dATP and the A(pA)3 tetramer core as substrates. In alternative, a synthetase can use dNTPs together with NAD + as substrates [48]. Therefore, the Ap4A alarmone can be converted also into oligo2-5A.…”
Section: Ap4a and Oligoadenylatesmentioning
confidence: 99%